The Efficacy of Group Cognitive-Behavioral Therapy Based on Lazarus\'s Multimodal Approach on Psychological Weakness and Thought Fusion Among Diabetic Patients - P Karimi Sani; SH Zeinali; SM Tabatabai; H Rostami; A Fathi; P Alamshahi Vayqan (Armaghane Danesh Bimonthly Journal, 2020)
Background & aim: Diabetes is as a chronic disorder, which produce lots of limitation in patientschr('39') activities and psychological quality. The aim of the present study was to investigate the efficacy of cognitive-behavioral therapy based on Lazaruschr('39')s multimodal approach to psychological weakness and thoughts fusion among diabetic patients with wounds.